Social hierarchy impacts response to reward downshift in sows - Ede, Thomas; Ibach, Sarah; Parsons, Thomas D. (Frontiers in Animal Science, 2025)
Pigs are social, hierarchical animals. Frequent mixing and regrouping of unfamiliar animals are common production practices that result in disruption and re-establishment of hierarchies. Little research has focused on the emotional component of this experience. Reward downshift paradigms have been investigated as a promising method for evaluating the affective state of animals. Therefore, we sought to evaluate responses to reward downshift as a method for evaluating the affective states of high vs. low-ranking sows. Pigs of either high (n = 8) or low (n = 9) social hierarchy (based on feed order) were enrolled. Pigs were initially trained to approach and consume a sweet sports drink (Gatorade, 5.8% sugar). The reward was then downshifted to a 1:10 diluted solution (0.58% sugar), and the approach latency, volume consumed, and peak force applied to the reward container were measured for each subject over a 3 min test for four consecutive days. Pigs of high social standing reacted to the downshift by decreasing their consumption both initially and over subsequent test days as well as slowing their approach to the reward over time. Low ranking sows also reduced their immediate consumption but did not show changes over the subsequent test days following the downshift. The reward appears to be valuable to low-rank animals regardless of its quality, potentially indicating lower reward expectations, value in the non-competitive access to a resource, or the stress-buffering action of the reward, possibly reflective of a relative negative affective state. Our findings suggest that reward valuation can be promising tool for the assessment of an animal’s affective states, but further research will be needed to fully understand its utility.